(untitled) (JURNAL ADMINISTRASI PUBLIK, 2019)
This study aims to determine the recruitment of the civil state apparatus at the regional employment board the city of manado, this research use apporoach qualitative description, the author rate is based on the recruitment procces with the data collected through interview techniques, observation, and dicumen of 5 informants yerkait directly with the implementation of the recruitment process of the civil state apparatus in the employment agency topography of the city of manado, based on research do then known there is good communication and clear abaot the process recruitment employees in the employment agency area of the city manado the availability of resources thant support such as human resources and infrastructure in the recruitment of employees, the level of honesty and commitment the employee-owned quite good. Not convoluted like the process of recruitment is done online to anticipate the collection of wild, felt already better, in terms of transparency and akuntabilitasi in the process of recruitment has been very good but there are still some things that need to be improved again for the fix kualitad existing employees Key Word : Rekruitment Of The State Civil Apparatus Staffing